2021
DOI: 10.1016/j.ijid.2021.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Gap to End-TB targets in eastern China: A joinpoint analysis from population-based notification data in Zhejiang Province, China, 2005–2018

Abstract: Background: Zhejiang is a southeastern province of China with middle level notification rates of tuberculosis in China, but more than 27,000 pulmonary tuberculosis (PTB) cases are still reported annually in this province. We aimed to analyze the time trends of PTB cases and bacteriologically confirmed cases notification rates at the province and city levels of Zhejiang during 2005-2018. Methods: Data from the web-based TB Information Management System of Zhejiang Province were used to calculate annual notifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
2
11
2
Order By: Relevance
“…This contrasted with a decreasing trend of total notified PTB cases during the study period. These results were in line with the findings of previous work ( 40 ). The decline of notified PTB incidence among students is likely due to the expanded DOTS strategy initiated since 2000 ( 41 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This contrasted with a decreasing trend of total notified PTB cases during the study period. These results were in line with the findings of previous work ( 40 ). The decline of notified PTB incidence among students is likely due to the expanded DOTS strategy initiated since 2000 ( 41 ).…”
Section: Discussionsupporting
confidence: 94%
“…The clustering period was concentrated only in the first 7 years. After 2014, no cluster was identified, which was attributed to efforts toward PTB prevention and intervention in the Zhejiang Province ( 40 ). For instance, comprehensive interventions entailing health policy making for PTB treatment and promotion the application of innovative technology enhanced PTB diagnosis and increased patients' adherence to the treatment, avoiding the potential clusters in the students eventually.…”
Section: Discussionmentioning
confidence: 99%
“…It could help to find meaningful turning points or trends in disease incidence and mortality over time. To the best of our knowledge, few studies have described TB incidence and mortality temporal variations in China using this model [ 3 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of age on LTBI was also seen in Brazil ( De Jezus et al., 2021 ) and Japan ( Ogawa et al., 2021 ). Compared to the younger in Zhejiang, not only the prevalence of LTBI but also the incidence of tuberculosis was high in older adults ( Zhu et al., 2021 ), which may be the result of the higher cumulative exposure risk and poor immunity with age increasing. Our study found male had a greater chance of TB infection than female, which was also supported in other countries ( Fernandes et al., 2018 ; Lwin et al., 2020 ).…”
Section: Discussionmentioning
confidence: 94%